Root and tuber crops for food security and income generation in Hunan, China: results of a scoping study - Li, H.; Xie, K.; Li, W.; Huang, B. (International Potato Center, 2017)
This scoping study is an initial activity of FoodSTART+ to assess the potential and opportunities of RTCs (root and tuber crops) to help enhance food resilience among the poor households in upland and coastal communities through collaborative research and development of RTCs innovations with IFAD investment projects.